Collective Agreements and Juridical Extension - Tremblay, Gérard (Relations industrielles / Industrial Relations, 1951)
SummaryAfter a brief outline of the historical evolution of the Collective Agreement Act since its adoption in 1934 and of the Labour Relations Act of 1944, the author examines in succession the contents, the authority and the application of these two laws. Both of them present certain difficulties in their application and thus cause differences in viewpoints between employers and employees. How can these differences be overcome ? There is the problem. The reader will find in this article a possible solution from the point of view of the law, union requirements and certain economic aspects, and two possible corrective measures that may be applied immediately.